Ultrafine Cellulose Nanofiber‐Assisted Physical and Chemical Cross‐Linking of MXene Sheets for Electromagnetic Interference Shielding (Small Methods 12/2021). Issue 12 (13th December 2021) - Wu, Na; Zeng, Zhihui; Kummer, Nico; Han, Daxin; Zenobi, Renato; Nyström, Gustav
Abstract : Structural Phase Transition In article number 2100889, Zeng, Zenobi, Nyström, and co‐workers have consolidated a combination of cellulose nanofibers from sustainable biomass and MXene nanosheets in densified, ultrathin and flexible composites with excellent electromagnetic interference shielding performance. These materials were assembled using scalable bottom‐up fabrication and a combination of physical and chemical crosslinking resulting in high mechanical strength and electrical conductivity MXene based macrostructures with potential application in next‐generation high‐performance electronic devices.